Remote sensing of atmosphere and underlying surface using radiation of global navigation satellite systems - Anh, Nguyen Xuan; I., Lutsenko V.; O., Popov D.; Chi, Cong Pham; Hoai, Trung Tran (Vietnam Journal of Marine Science and Technology, 2017)
This paper is devoted to solving the problem of atmosphere diagnosis using radiation of the global navigation satellites. New methods for diagnosing the meteorological situation, the refractive state of the troposphere and underlying surface based on the behavior of navigation signals are proposed. The model of the mapping function that takes into account the sphericity of the troposphere and allows more accurate describing of the actual values for the tropospheric delay is proposed